2022
DOI: 10.3390/biomedicines10081862
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids—Perspectives for Individual Treatment in Selected Patients: Analysis of the Case Series

Abstract: Cannabinoids can be successfully used in the treatment of many symptoms and diseases; however, most often they are not the drugs of first choice. They can be added to the primary therapy, which can improve its effectiveness, or be introduced as the basic treatment when the conventional methods have failed. Small clinical trials and case reports prove the benefits of applying medicinal cannabis in various indications; however, clinical trials in larger groups of patients are scarce and often controversial. Due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
3
0
1
Order By: Relevance
“…Cannabidiol and tetrahydrocannabinol are cannabinoid compounds that have demonstrated analgesic efficacy in chronic neuropathic pain treatment [ 11 ], and their combinations with other drugs also suggest a promising role as anti-inflammatories [ 12 ] or as drugs for cancer therapy [ 13 , 14 ], migraine [ 15 ], opioid and alcohol dependence [ 16 ]. The psychoactive effects of THC have been a major limitation to the cannabinoids’ medicinal use, but the emergence of new varieties of plants with high-CBD and low-THC content opens a new window of opportunities for their use in many countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cannabidiol and tetrahydrocannabinol are cannabinoid compounds that have demonstrated analgesic efficacy in chronic neuropathic pain treatment [ 11 ], and their combinations with other drugs also suggest a promising role as anti-inflammatories [ 12 ] or as drugs for cancer therapy [ 13 , 14 ], migraine [ 15 ], opioid and alcohol dependence [ 16 ]. The psychoactive effects of THC have been a major limitation to the cannabinoids’ medicinal use, but the emergence of new varieties of plants with high-CBD and low-THC content opens a new window of opportunities for their use in many countries.…”
Section: Discussionmentioning
confidence: 99%
“…All these medicines together with medical cannabis have demonstrated analgesic efficacy in chronic neuropathic pain treatment [ 11 ]. In addition, an increasing number of cannabinoids and their combinations seem promising as anti-inflammatory drugs [ 12 ], in cancer therapy [ 13 , 14 ], migraine [ 15 ], opioid and alcohol dependence treatment [ 16 ]. It has been shown that very low doses of THC + CBD and THCA + CBDA combinations have an anti-emetic effect [ 17 ] which is an example of a combination use advantage when compared to the administration of high doses of a single active component.…”
Section: Introductionmentioning
confidence: 99%
“…Najczęściej kannabinoidy dodaje się do stosowanych wcześniej analgetyków i koanalgetyków, co daje możliwość ograniczenia ich dawek lub w wybranych przypadkach całkowite odstawienie. Rzadko zatem kanabinoidy stosowane są w monoterapii i nie jest to powszechnie zalecana praktyka [29,[43][44][45][46][47].…”
Section: Zastosowanie Kannabinoidów W Leczeniu Bólu Przewlekłegounclassified
“…Research suggests that CBD, in particular, may have anxiolytic and antidepressant effects, potentially beneficial for conditions such as anxiety and depression [16,17]. However, the relationship between cannabis use and psychiatric disorders is complex, with some studies indicating that excessive or inappropriate use of cannabis may exacerbate symptoms of these conditions or contribute to the onset of disorders in vulnerable individuals [18,19]. Therefore, careful clinical assessment and monitoring are essential when considering cannabis-based treatments for psychiatric disorders.…”
Section: Medical Marijuana-basic Information Effects On the Human Bod...mentioning
confidence: 99%